WATER DRIVE OIL FIELD PRODUCTION STRATEGY TO REDUCE THE POSSIBILITY OF WATER PRODUCTION PROBLEMS - Rizkiaputri, Chintya
Most oil company produces their field to achieve production rate as high as possible. This “high oil rate” policy is used in order to achieve faster return of investment. However, the production strategy in water drive reservoir must be closely paid attention because the way the oil produced will greatly affect the production of water. Water drive mechanism closely relates to the movement of water into the reservoir as oil produced. This type of reservoir tends to have water production increase through time as the water encroaches into reservoir zone. Production without rate constraint will result to faster water breakthrough so that the water cut will increase rapidly. This increase, if not predicted in the beginning, will lead to the under capacity of water treatment in the future. Production without rate constraint will also affect the oil treatment capacity since the oil production rate will be higher in the beginning and decline significantly through time. Therefore, a rate constraint in the field is needed.